Bio-inspired Synthesis of Ag, Au, and Ag-Au Bimetallic Nanoparticles using Capsicum annuum Aqueous Leaf Extract and Assess their In-vitro Antibacterial and Anticancer Potential (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Noble bimetallic nanoparticles (BNPs) exhibit strong anticancer and antibacterial activities. They are known to be stable, less toxic, environmental friendly and biocompatible nature. Due to their enhanced biological properties, they are well suits for the biomedical applications such as cancer therapy, gene therapy and drug delivery. In the current study, we examine the anticancer and antibacterial potential of bio-mediated mono and bimetallic nanoparticles. Here, aqueous Capsicum annuum leaf extract was employed as a good reducing and capping agent for producing Ag, Au monometallic, and Ag-Au bimetallic nanoparticles. The formation of C.A- Ag, Au MPNs and Ag-Au BNPs was initially confirmed by visible color change of the reaction mixture and UV-Visible spectra show the Surface Plasmon Resonance (SPR) band observed at 543 nm. Furthermore, phytofabrication, crystallinities, structural alignments, particle size and elemental composition were studied by following standard physico-chemical techniques such as FT-IR (Fourier Transform Infrared), XRD (X-Ray diffraction), HR-TEM (High resolution-Transmission Electron Microscopy), SEM-EDX (Scanning Electron Microscopy and Energy- dispersive X-Ray Spectroscopy) respectively. The results were obtained from various characterization techniques confirmed that the C.A. mediated Ag, Au MNPs and Ag-Au BNPs were spherical in shape and FCC structure with nanoscale range (10-25 nm). The BNPs exhibit strong efficacy against bacterial strains. These nanoparticles were subjected to investigate the anticancer activity against human lung cancer cells (A549 cell line) through MTT assay. The cell viability was determined by this assay. The occurrence of cell apoptosis and necrotic were quantified by using dual fluorescent staining (AO/EB) and flow cytometry analysis. However, Ag-Au bimetallic nanoparticles showed highest cytotoxic potential with low IC50 - 57.35 ± 0.05 µM values. This IC50 value is comparatively lower than, Ag, Au MNPs and C.A. aqueous leaf extract. IC50 values of C.A- Ag-Au BNPs predominantly induced the cell apoptosis, necrotic and the death of A549 cells suggested the anticancer potential of C.A. mediated Ag-Au BNPs to treat the lung cancer cells.